Antibiotic resistance, integrons and Salmonella genomic island 1 among Salmonella Schwarzengrund in broiler chicken and pig - Yu-Chih Wang; Yi-Chih Chang; Hsiao-Li Chuang; Chien-Chao Chiu; Kuang-Sheng Yeh; Chao-Chin Chang; Ter-Hsin Chen (African Journal of Pig Farming, 2017)
Salmonella Schwarzengrund is an infrequent serovar isolated from humans in Taiwan. However, this serovar is which is highly invasive, is found in humans as report by two independent epidemiologic surveys. The present study delineated the widespread resistance to fluoroquinolone in S. Schwarzengrund isolated from both poultry and swine carcesses in Taiwan. We conducted the present study to investigate the prevalence and characteristics of S. Schwarzengrund isolated from broiler chicken in central Taiwan. A total of 187 S. Schwarzengrund isolates was gotten from slaughtered chicken and pigs in central Taiwan between June 2006 and March 2007. The percentages of resistance were as follows: ampicillin (90.74%), chloramphenicol (69.75%), florfenicol (24.07%), streptomycin (91.98%), trimethoprim and sulfamethoxazole (91.36%), nalidixic acid (96.30%), ciprofloxacin (8.02%), tetracycline (95.68%), amikacin (8.64%), ceftiofur (0.62%) and ceftriaxone (0%). Four types of class 1 integrons were detected: 1.2 kb carried blaPSE-1, aadA2 gene (n = 2), 1.2 kb carried blaPSE1, dfraA1 gene (n = 2), 1.0/1.2 kb carried blaPSE-1, aadA2 ( n = 2) and 1.9 kb carried dfrA12, aadA2 gene (n = 152). XbaI-digested PFGE patterns generated related clusters implicated in the dissemination of integron. Thirteen ciprofloxacin-resistant isolates were all detected in 5 identical mutations in the QRDR of gyrA, parC and parE. Our results suggest that there is a risk of transmitting multidrug resistant Salmonella between pig and chicken farms, and also suggest that there is a need to prevent the transmission of this organism from a neighboring contaminated farm.